2006
DOI: 10.1007/s10705-005-5630-4
|View full text |Cite
|
Sign up to set email alerts
|

What role can planted fallows play in the humid and sub-humid zone of West and Central Africa?

Abstract: Crop management without fertilizer input, which is commonly practiced by most farmers in the humid forest zone of West and Central Africa, requires soil fertility replenishment during a fallow period. Hypothetical relationships between fallow length and crop yields assume, that after the cropping phase replenishment starts with high annual increments, leading to an early recovery of most soil fertility, then slowly approaching a maximum level. The few available empirical data, however, indicate that this assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 71 publications
1
30
0
2
Order By: Relevance
“…These results are similar to others showing no improvement over a bush fallow of legume tree fallows (Leucaena and pigeon pea) in northern Laos (Roder and Maniphone 1998;Roder et al 1998;Saito et al 2008). A review article on planted tree fallows in West Africa also reported that in 60% of cases, crop yields following tree-based fallows were not different from those of the control (Hauser et al 2006). Good management during the rice growing season involves maintaining a low stem density at less than 0.22 stems m -2 and pruning branches (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are similar to others showing no improvement over a bush fallow of legume tree fallows (Leucaena and pigeon pea) in northern Laos (Roder and Maniphone 1998;Roder et al 1998;Saito et al 2008). A review article on planted tree fallows in West Africa also reported that in 60% of cases, crop yields following tree-based fallows were not different from those of the control (Hauser et al 2006). Good management during the rice growing season involves maintaining a low stem density at less than 0.22 stems m -2 and pruning branches (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…It is a multipurpose tree with the inner bark used to make paper, the stems for firewood, and the leaves for animal feed. The recent development of domestic processing industries and improved market channels have encouraged farmers to grow paper mulberry as a cash crop (Hamman 2001). …”
mentioning
confidence: 99%
“…In parts of West, Central, East and southern Africa, where the fallow periods have been shortened and cultivation has been extended for more than 2 years, maize yields generally decline rapidly (Drechsel et al 1996;Hauser et al 2006;Mafongoya et al 2006). Although use of inorganic fertilizer can overcome the problem, most smallholder farms use little or no mineral fertilizer (Mwangi 1999).…”
Section: Introductionmentioning
confidence: 99%
“…L'analyse du sol (Tableau 1) montre d'ailleurs que la matière organique du sol est plus élevée à Ekona qu'à Ongot. Bien que le manioc soit connu pour croître dans les sols très pauvres (Hauser et al, 2006 ;Echebiri et Edaba, 2008), un sol riche en éléments minéraux favorise sa croissance.…”
Section: Discussionunclassified